Investigation of foreign subsidiaries in the domestic stock markets. - Khor, Boon Keng. (2008)
Mainstream studies with regards to cross border listings focused primarily on the dual-listing of stocks in foreign and domestic markets. This paper extends on these studies by conducting an exploratory research in the area of foreign subsidiaries listed in domestic exchanges, namely Singapore (SGX), Hong Kong (HKEX) and Tokyo (TSE).